2012
DOI: 10.1523/jneurosci.2664-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Rebalance of Striatal NMDA/AMPA Receptor Ratio Underlies the Reduced Emergence of Dyskinesia During D2-Like Dopamine Agonist Treatment in Experimental Parkinson's Disease

Abstract: Here we show that the striatal NMDA/AMPA receptor ratio and the AMPA receptor subunit composition are altered in experimental parkinsonism in rats. Surprisingly, while L-DOPA fails to restore these critical synaptic alterations, chronic treatment with pramipexole is associated not only with a reduced risk of dyskinesia development but is also able to rebalance, in a dose-dependent fashion, the physiological synaptic parameters, thus providing new insights into the mechanisms of dyskinesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 62 publications
5
53
0
Order By: Relevance
“…However, using physiological recordings and dendritic reconstruction techniques, recent studies have revealed that iSPNs undergo profound structural-functional adaptations in LID models (38,45). Moreover, several studies have reported D2 agonist-induced dyskinesias in experimental models of PD (46)(47)(48). These considerations highlight the importance of testing the causality of dSPN and iSPN activity in the genesis of parkinsonian hypokinesia and dyskinesia.…”
Section: Discussionmentioning
confidence: 99%
“…However, using physiological recordings and dendritic reconstruction techniques, recent studies have revealed that iSPNs undergo profound structural-functional adaptations in LID models (38,45). Moreover, several studies have reported D2 agonist-induced dyskinesias in experimental models of PD (46)(47)(48). These considerations highlight the importance of testing the causality of dSPN and iSPN activity in the genesis of parkinsonian hypokinesia and dyskinesia.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, treatment with L-DOPA did not reduce inwardrectifying AMPAR currents induced by 6-OHDA-lesion. However pramipexole, which was shown to have antiparkinsonian effects and be associated with reduced dyskinesia, could reverse the alteration of glutamatergic transmission as well as restore rectification values to control levels (Bagetta et al, 2012). Controlling the CP-AMPAR content of synapses may therefore be critical to treating striatal motor dysfunctions.…”
Section: Discussionmentioning
confidence: 99%
“…Herein, we show that transplanted DA neurons are able to integrate into the host brain microcircuit, restoring corticostriatal synaptic plasticity in a highly reinnervated region. In experimental animal models, PD symptoms are linked to alterations in both LTP and LTD (25,26,35). Thus, the ability to restore corticostriatal synaptic plasticity could help determine the therapeutic potential of novel interventions, including cell transplants.…”
Section: Discussionmentioning
confidence: 99%